Does dysfunctional behavior matter when it comes to audit quality in Malaysia? - Tze, San Ong; Boon, Heng Teh; Geok, Kim Sim; Sin, Huei Ng; Hossain, Mohammad Imtiaz (UKM Press, 2022)
Audit quality is becoming a concern and a problematic issue due to corporate scandals in the business sector. The auditors were accused of incompetence and lack of independence in detecting fake financial reporting, which led to the company's failure. The dysfunctional auditors' behaviour has an impact on audit quality. As a result, this study aims to scientifically investigate and analyse the elements that may lead to dysfunctional auditor conduct and decreased audit quality. The factors addressed include time constraints, task complexity, and client importance on dysfunctional auditor behaviour and audit quality in the Malaysian setting. A total of 133 respondents were involved in this survey, selected by the snowball sampling method. The results reveal the propensity of individual auditors to accept dysfunctional behaviour due to time, budget pressure, and task complexity. Surprisingly, client importance does not impair auditors' independence. Auditors play an essential role in maintaining the quality of audit reports and restoring public trust in the audit profession since auditors are granted credibility to assure financial accounts. As a result, this paper has important implications. It provides valuable insight for Malaysian regulators and audit firms to identify factors influencing dysfunctional auditor behaviour and deterioration of audit quality and develop various approaches to address these issues while maintaining the value of an audit for external users